Performance improvement of commercial ISFET sensors using reactive ion etching - Panteli,C; Georgiou,P; Fobelets,K (Microelectronic Engineering, 2018)
Reactive Ion Etching (RIE) is used to improve the performance of commercial Complementary Metal Oxide Semiconductor (CMOS) Ion-Sensitive Field-Effect Transistors (ISFETs) by thinning the top passivation layers inherent of the CMOS fabrication process. Using a combination of O2 and SF6 in 50% ratio, both polyimide and Si3N4 layers are etched in one etching step. Etching for different times we find the right remaining layer thickness for best ISFET performance to be ∼1 μm of SiO2. The results show an increase in pH sensitivity of 125%, a 5700% increase in passivation capacitance and a 96% reduction in capacitive attenuation. The RIE etch recipe can be used on multi-project wafers (MPW) to boost CMOS sensor performance.